Sexualité et espace public : visibilité lesbienne dans le cinéma récent - Nadeau, Chantal (Sociologie et sociétés, 1997)
Dans cet article, l'auteure démontre que la circulation et la consommation croissante des images lesbiennes dans l'espace public participent du phénomène complexe d'une culture du visible. Tout en soulignant les inévitables compromis qui découlent d'une telle négociation de la visibilité, elle retrace le potentiel culturel qu'une telle marchandisation de la " différence " représente pour les lesbiennes. L'identité et le désir lesbiens sont donc analysés ici en tant que produits représentationnels aptes à être consommés autant par les hétérosexuel.les que par les lesbiennes. Par une analyse des diverses stratégies de négociation du désir lesbien tirées de deux films populaires tant auprès d'un public hétérosexuel que gai (Gazon maudit et When Night is Falling), la critique confronte la matérialité de l'identité lesbienne au cinéma à la valeur de l'image saphique sur le marché de l'identité.
Keywords: approches et analyses; cinéma; corps; discipline; hétérosexisme; identités LGBTQIA2+; personnes lesbiennes; ressource en ligne; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

Daughters of the dust - Dash, Julie (Cohen Film Collection, 1991)
At the dawn of the 20th century, a multi-generational family in the Gullah community on the Sea Islands off of South Carolina – former West African slaves who adopted many of their ancestors’ Yoruba traditions – struggle to maintain their cultural heritage and folklore while contemplating a migration to the mainland, even further from their roots. The first wide release by a black female filmmaker, DAUGHTERS OF THE DUST was met with wild critical acclaim and rapturous audience response when it initially opened in 1991. Casting a long legacy, DAUGHTERS OF THE DUST still resonates today, most recently as a major in influence on Beyonce’s video album Lemonade. Winner of the Cinematography Award and nominated for the Grand Jury Prize in the Dramatic competition at the Sundance Film Festival. Chosen for preservation by the National Film Preservation Board, USA
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; cinéma; communication; cours; discipline; discours dominant; esclavagisme; fem3200; histoire et politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

A lure of knowledge: Lesbian sexuality and theory - Roof, Judith (Between men-between women, 1991)
Lesbianism in literature has been dealt with rather indirectly in the past. Editors have led readers to the "artistry" of a work containing lesbianism, emphasizing instead the literary history and historical context of the work rather than the representations of lesbianism. The editor for Colette's The Pure and the Impure, for instance, affirms that Colette has a knowledge of a "strange sisterhood," but assures readers she has never strayed from the "normal." In the groundbreaking A Lure of Knowledge, Judith Roof demonstrates that representations of lesbian sexuality occupy specific locations or positions in the arguments, subject matter, and rhetoric of Western European and American literary criticism. She examines the political context of representations: how lesbian sexuality is used as a signifier an why it appears when and where it does. Roof argues that attempts to depict or explain lesbian sexuality spur anxieties about knowledge and identity. In reaction to and denial of these anxieties, lesbian sexuality is represented in film, literature, theory, and criticism as foreplay, as simulated heterosexuality, as erotic excess, as joking inauthenticity, as artful compromise, or as masculine mask in a specific repertoire of neutralization and evasion. Challenging the heterosexism of film theory and feminist theory, this book analyzes the rhetorical use of lesbian sexuality. Roof explores a range of discourses, from the woks of such authors as Anais Nin, Olga Broumas, Julia Kristeva, Jane Rule, Luce Iriguray, and Sigmund Freud, to films such as Emmanuelle, Desert Hearts, Entre Nous, and I've Heard the Mermaids Singing, to professional tennis.
Keywords: approches et analyses; arts; cinéma; communication; discipline; hétérosexisme; lesbianisme; personnes lesbiennes; sexualité; sexualité lesbienne; systèmes d'oppressions; thématiques; études culturelles; études littéraires